2012
DOI: 10.4149/bll_2012_093
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency – a possible link between osteoporosis and metabolic syndrome

Abstract: Abstract:Objectives: The aim of our study was to evaluate the relationship between bone mineral density (examined by DXA -dual energy x-ray absorptiometry), vitamin D 3 levels and the signs of metabolic syndrome. Methods: We examined 55 subjects (37 women, 18 men, age median 67.8 years) with no history of osteoporosis, suffering from metabolic syndrome (defi ned as abdominal obesity and more than 2 of other componentsarterial hypertension, dyslipidemia and diabetes mellitus or impaired glucose tolerance, accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Apart from the relation of a low serum level of 25-OHD to greater bone turnover, bone loss and OS, it is in an inverse association with BMI [ 4 , 19 , 20 ]. It has been calculated in multivariate analysis that a decrease of 0.74 nmol/l in 25-OHD causes an increase in BMI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the relation of a low serum level of 25-OHD to greater bone turnover, bone loss and OS, it is in an inverse association with BMI [ 4 , 19 , 20 ]. It has been calculated in multivariate analysis that a decrease of 0.74 nmol/l in 25-OHD causes an increase in BMI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency results in bone loss and increased inflammation through its immunomodulatory effects. [ 12 13 14 ] Recent data suggested that Vitamin D deficiency may play a role both in periodontal disease and DM. [ 14 15 16 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nonhereditary factors include alteration of hormone levels, aging, and increased oxidative stress . 1,25‐Dihydroxyvitamin D [1,25(OH) 2 D] is an important factor for optimal bone health . Vitamin D, synthesized in skin tissue or absorbed via the intestine, is first metabolized by the action of liver 25‐hydroxylase, to 25‐hydroxyvitamin D [25(OH)D], which is then converted, by the action of renal 1α‐hydroxylase (encoded by Cyp27b1 ), or of extrarenal Cyp27b1 to active 1,25(OH) 2 D. This moiety then exerts its action by binding to the vitamin D receptor (VDR) .…”
Section: Introductionmentioning
confidence: 99%
“…(2) 1,25-Dihydroxyvitamin D [1,25(OH) 2 D] is an important factor for optimal bone health. (3) Vitamin D, synthesized in skin tissue or absorbed via the intestine, is first metabolized by the action of liver 25-hydroxylase, to 25-hydroxyvitamin D [25(OH)D], which is then converted, by the action of renal 1α-hydroxylase (encoded by Cyp27b1), or of extrarenal Cyp27b1 (4,5) to active 1,25(OH) 2 D. This moiety then exerts its action by binding to the vitamin D receptor (VDR). (6,7) Our previous studies, using double homozygous knockout of Cyp27b1 and the parathyroid hormone gene (Pth) or double homozygous knockout of Cyp27b1 and the calcium sensitive receptor gene (Casr), demonstrated that endogenous and exogenous 1,25(OH) 2 D could directly stimulate osteoblastic bone formation via the VDR.…”
Section: Introductionmentioning
confidence: 99%